Modern Bashkir prose: genre and fiction peculiarities - Akhmadiev, Rif B.; Kulsarina, Irena G.; Khuzhakhmetov, Ainur O. (Opción, 2019)
The purpose of this article is to consider the genre, fiction and plot peculiarities of provincial literature through the Bashkir writers via the methodology of structural-functional, institutional and phenomenological approaches. The system analysis method was used to achieve this goal. In analyzing the literary works of Bashkir writers, we have allocated the main peculiarities of provincial literature. As a result, modern literary criticism assigns a significant place to provincial literature as the main source of culture. In conclusion, modern Bashkir prose vividly reflects the provincial literature development in a multicultural state